Assessment of Projected Temperature and Precipitation in the Northern Province of Sri Lanka through Statistically Downscaled CMIP6 Projection - Piratheeparajah, N. (Geoecology, 2024)
The issue of climate change has emerged as a paramount concern for the global community, with several nations grappling with the far-reaching effects thereof on their re spective territories. Among these nations, Sri Lanka is ranked as the country facing the greatest potential threat. In the Northern Province of Sri Lanka, which has experienced a rebirth after years of internal conflict with the aid of international agencies, projections regarding climate change indicate a diverse array of potential impacts. To arrive at these projections, a comprehensive analysis was conducted, which leveraged downscaled data derived from the Coupled Model Inter-comparison Projects, Phase 6 (CMIP6), obtained via the grid for the Northern Province. Various models were employed to scrutinize this data, and to validate the findings, an analysis was performed by comparing the model-simulated past climate data to observed data. Multimodal ensembles provided insights into unique temperature and precipitation patterns under varying emis sion scenarios, including the Shared Socioeconomic Pathways (SSP) 4.5 and 8.5, between 2020 and 2100. Under the SSP2 4.5 scenario, for instance, the temperature increase would total 1.13°C, accompanied by 106.19mm of augmented rainfall. By contrast, under the SSP5-8.5 scenario, temperature would increase by 1.81°C, with a projection of 159.6mm increase in rainfall. Moreover, spatially, the future changes in temperature and rainfall for the Northern Province of Sri Lanka display consequential variations. Specifically, the western part is projected to witness higher rates of temperature and rainfall increase than the eastern part. However, it should be noted that variations exist in the values of the projections of temperature and rainfall across the different models. Regardless, the region must brace itself for elevated temperatures, resulting in heatwaves and an augmented frequency of scorching days, indicating an urgent need for policymakers and communities to incorporate these findings when developing and implementing climate adaptation strategies that aim to mitigate climate change’s adverse impact in the area of study.
Keywords: Temperature; Rainfall; Multimodel; Ensemble; Increasing; Northern Sri Lanka